STUDY OF SOIL CHARACTERISTICS IN PLANTS MANAU RATTAN (Calamus manan) SIGAPOKNA RURAL DISTRICTS SIBERUT MENTAWAI ISLANDS WEST DISTRICT - Sri Yanti, Mira; Dasrizal, Dasrizal; Prari Keslan, Widya (Pendidikan Geografi, 2014)
Abstracts This study aims to describe the characteristics of the soil at the plant in the village of Rattan manau Sigapokna Western District of Siberut Mentawai Islands by force and physic condition  landforms and soil chemistry. This research is descriptive method used is the survey method, the data source is the primary data collected directly in the field and in the laboratory, while secondary data is a source of reference and analysis obtained from this research that library. Technique using purposive random sampling. Data  technique  analysis that soil characteristics were analyzed descriptively and ditabulasi of the data unit of criteria for the determination of landforms and soil physical and chemical conditions were analyzed and in process. The results of the study explains that : the characteristics of the soil in the study area on 3 landform units namely : ( 1 ) Unit of landforms in the study area in the form of units of fluvial landforms and landform units Consist yesterday with 20 units of land, fluvial landform units contained in the unit terrain F3.I.Kc . Tmpsa.Org and F4.I.Kc.Tmps.Org , landform units can marinter M5.I.Kc.Tmpsa.Org on land units . ( 2 ) physical and chemical condition of the soil in the area of the sample is ( 1 ) silty clay soil texture , ( 2 ) blocky soil structure , ( 3 ) low organic matter and slightly lower from 0.64 to 2.70 , ( 4 ) poor soil pH 4.43 to 4.79 , ( 5 ) slow soil permeability from 0.11 to 1.19 , ( 6 ) poor drainage . Limiting factor of plant cane manau ( calamus manan ) ie organic material needed for manau rattan plant is fertile soil, loose and rich in organic matter, pH needed for plant rattan manau soil with a pH of 5.1 to 5.8 is not too acidic and alkalis and required drainage is good soil drainage.